MENINGKATKAN PRESTASI BELAJAR SISWA KELAS IXA PELAJARAN PENDIDIKAN KEWARGANEGARAAN MELALUI MODEL PEMBELAJARAN MIND MAPPING DI MTsN 4 GUNUNGKIDUL - ANI SUSILAWATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
This study aims to improve the learning achievement of class IXA students at MTsN 4 Gunungkidul for the 2022/2023 academic year by using the Mind Mapping model. The hypothesis of this classroom action research is: learning using the Mind Mapping model can improve student achievement in class IXA on Basic Competency 3.4 Analyzing the principle of unity in ethnic, religious, racial and inter-group diversity (SARA), social, cultural, economic, and gender within the framework Bhinneka Tunggal Ika at MTs Negeri 4 Gunungkidul. During the learning process, observations were made of the teacher's performance as a researcher and cognitive and affective assessments of students were carried out through observation sheets and assessments/daily tests. Other findings during the learning process were discussed between the researcher and the observer, supplemented by observational data that were reflected in each cycle. Research results in cycle I and cycle II show an increase in student learning outcomes with the assumption that student learning outcomes increase, learning achievement also increases. The results of the assessment of student learning outcomes are: cycle I: observation of student attitudes shows achievement of 65.68% with good criteria and completeness of cognitive scores reaches 67.64% with good criteria Cycle II: results of observation of attitudes reach 81.37% with very good criteria and completeness of cognitive value reached 82.35% with very good criteria. This study aims to determine the effectiveness of the Mind Mapping model in improving student achievement. ABSTRAKPenelitian ini bertujuan untuk meningkatkan prestasi belajar siswa kelas IXA MTsN 4 Gunungkidul tahun pelajaran 2022/2023 dengan menggunakan model Mind Mapping. Adapun hipotesis penelitian tindakan kelas ini adalah: pembelajaran menggunakan model Mind Mapping dapat meningkatkan prestasi belajar siswa kelas IXA pada Kompetensi Dasar 3.4 Menganalisis prinsip persatuan dalam keberagaman suku, agama, ras antar golongan (SARA), sosial, budaya, ekonomi, dan gender dalam bingkai Bhinneka Tunggal Ika di MTs Negeri 4 Gunungkidul. Selama proses pembelajaran, dilakukan pengamatan terhadap kinerja guru sebagai peneliti dan dilakukan penilaian kognitif dan afektif siswa melalui lembar observasi dan penilaian/ulangan harian. Temuan lain selama berlangsungnya pembelajaran didiskusikan antara peneliti dengan observer dilengkapi dengan data hasil pengamatan yang dilakukan refleksi pada setiap siklusnya. Hasil Penelitian pada siklus I dan siklus II menunjukkan adanya peningkatan hasil belajar siswa dengan asumsi hasil belajar siswa meningkat maka prestasi belajar juga meningkat. Hasil Penilaian terhadap hasil belajar siswa adalah: siklus I: observasi sikap siswa menunjukkan pencapaian 65,68% dengan kriteria baik dan ketuntasan nilai kognitif mencapai 67,64% dengan kritria baik Siklus II: hasil obsevasi sikap mencapai 81,37% dengan kriteria sangat baik dan ketuntasan nilai kognitif mencapai 82,35% dengan kriteria sangat baik. Penelitian ini bertujuan untuk mengetahui keefektifan model Mind Mapping dalam meningkatkan prestasi belajar siswa.